Multi‐Watt high‐power THz frequency quantum cascade lasers. Issue 12 (1st June 2017) - Li, L.H.; Chen, L.; Freeman, J.R.; Salih, M.; Dean, P.; Davies, A.G.; Linfield, E.H.
Abstract : Multi‐Watt high‐power terahertz (THz) frequency quantum cascade lasers are demonstrated, based on a single, epitaxially grown, 24‐μm‐thick active region embedded into a surface‐plasmon waveguide. The devices emit in pulsed mode at a frequency of ∼4.4 THz and have a maximum operating temperature of 132 K. The maximum measurable emitted powers from a single facet are ∼2.4 W at 10 K and ∼1.8 W at 77 K, with no correction being made for the optical collection efficiency of the apparatus, or absorption by the cryostat polyethylene window.